PreC and C Regions of Woodchuck Hepatitis Virus Facilitate Persistent Expression of Surface Antigen of Chimeric WHV-HBV Virus in the Hydrodynamic Injection BALB/c Mouse Model - Weimin Wu; Yan Liu; Yong Lin; Danzhen Pan; Dongliang Yang; Mengji Lu; Yang Xu (Viruses, 2017)
In the hydrodynamic injection (HI) BALB/c mouse model with the overlength viral genome, we have found that woodchuck hepatitis virus (WHV) could persist for a prolonged period of time (up to 45 weeks), while hepatitis B virus (HBV) was mostly cleared at week four. In this study, we constructed a series of chimeric genomes based on HBV and WHV, in which the individual sequences of a 1.3-fold overlength HBV genome in pBS-HBV1.3 were replaced by their counterparts from WHV. After HI with the WHV-HBV chimeric constructs in BALB/c mice, serum viral antigen, viral DNA (vDNA), and intrahepatic viral antigen expression were analyzed to evaluate the persistence of the chimeric genomes. Interestingly, we found that HI with three chimeric WHV-HBV genomes resulted in persistent antigenemia in mice. All of the persistent chimeric genomes contained the preC region and the part of the C region encoding the N-terminal 1–145 amino acids of the WHV genome. These results indicated that the preC region and the N-terminal part of the C region of the WHV genome may play a role in the persistent antigenemia. The chimeric WHV-HBV genomes were able to stably express viral antigens in the liver and could be further used to express hepadnaviral antigens to study their pathogenic potential.